Therapeutic Effect of CAOLD Chemotherapy Regimen on Patients With Relapsed/Refractory Angioimmunoblastic T-Cell Lymphoma: A Case Study - Liu, Yu; Li, Pingping; Qian, Liren (Frontiers in Oncology, 2022)
Angioimmunoblastic T-cell lymphoma (AITL) is a kind of peripheral T-cell lymphomas (PTCLs) with a highly invasive feature. At present, patients are often treated with CHOP or CHOP-like regimens which is of poor prognosis whilst having high recurrence rate. Once the patient fails to achieve remission or relapse after the first-line treatment, many salvage chemotherapy regimens are always ineffective, and the long-term survival will be difficult to achieve for them. In this circumstance, more effective therapy methods are needed. In this study, two patients with relapsed/refractory AITL were treated with the CAOLD regimen [cyclophosphamide 400 mg/m2 qd d1, cytarabine 30 mg/m2 qd d1–d4, vindesine 2 mg/m2 qd d1, pegaspargase (PEG-ASP) 2,500 IU/m2 qd d2, dexamethasone 7.5 mg/m2 qd d1–d5], and long-term remission was achieved after chemotherapy. One is still alive after achieving complete remission (CR) after two cycles of chemotherapy, who has been followed up for 82 months. Besides, another patient achieved partial remission (PR) after the first course of chemotherapy. Then, CR was obtained after four courses of consolidation chemotherapy. The patient has been followed up for 63 months and is still alive. Both of them achieved long-time survival. These two successful cases demonstrated that the CAOLD regimen can be a better choice for relapsed/refractory AITL and offers hope of breakthrough in this medical field.